The Role of Family, Education, and Cultural Context in Shaping Ethical Development among Nigerian Children: Challenges and Opportunities - Abdulkareem, Habibat Bolanle; Abdulkareem, Rukayat Adetoun; Dawodu, Muhammad Saheed; Oreagba, Fatima (EduBasic Journal: Jurnal Pendidikan Dasar, 2025)
Ethical development in children is pivotal for shaping societies grounded in integrity, empathy, and social responsibility. In the Nigerian context, this development is shaped by the dynamic interplay of family structures, educational systems, and cultural values. This literature review critically examines existing research on how these factors collectively influence moral growth among Nigerian children. Emphasis is placed on the family as the foundational unit of moral transmission, highlighting the impact of parenting styles, religious practices, and communal values. The review also explores the role of the educational system in promoting ethical reasoning through formal curricula, character education, and community service while acknowledging systemic challenges such as teacher capacity, curriculum gaps, and institutional corruption. Cultural influences, including traditional African ethics, religious teachings, and the pressures of globalization and digital media, are analyzed to understand their complex effects on children's moral orientation. Drawing on peer-reviewed journal articles, policy documents, and empirical studies, the review adopts an integrative approach to synthesizing both indigenous and global perspectives. However, it recognizes limitations in the existing literature, including a scarcity of Nigeria-specific empirical studies, uneven methodological rigor, and the underrepresentation of indigenous moral frameworks. By addressing these gaps, this review aims to provide both theoretical insight and practical recommendations. It advocates a multidimensional strategy that reinforces family engagement, integrates culturally relevant moral education, and mobilizes religious and societal institutions. Ultimately, this literature review offers a contextual blueprint for nurturing a morally resilient generation equipped to navigate the ethical complexities of contemporary Nigerian society